2007
DOI: 10.1021/ma0623993
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation Effects in the Theory of Microphase Separation of Diblock Copolymers in the Presence of an Electric Field

Abstract: We generalize the Fredrickson-Helfand theory of the microphase separation in symmetric diblock copolymer melts by taking into account the influence of a time-independent homogeneous electric field on the composition fluctuations within the self-consistent Hartree approximation. We predict that electric fields suppress composition fluctuations, and consequently weaken the first-order transition. In the presence of an electric field the critical temperature of the order-disorder transition is shifted towards its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…26 It was also predicted for block copolymer melts as a result of suppression of the composition fluctuations by electric field (static treatment), 27 which we do not consider here.…”
Section: Resultsmentioning
confidence: 82%
“…26 It was also predicted for block copolymer melts as a result of suppression of the composition fluctuations by electric field (static treatment), 27 which we do not consider here.…”
Section: Resultsmentioning
confidence: 82%
“…The weak first-order phase transition occurring in short polymers is shifted closer to the mean-field value, that is, the ODT point is shifted to higher temperatures (Gunkel et al, 2007;Stepanow and Thurn-Albrecht, 2009). As a result, phase separation is favored even if ε = 0.…”
Section: B Block-copolymer Phase Transitionsmentioning
confidence: 92%
“…As for the melt of block copolymers, the lamellar microdomains have been found to orient parallel to the electric fields [11,[47][48][49][50][51][52][53][54][55] when the disordered melt was cooled down below T ODT in the presence of the electric fields. It has been also found that cylindrical microdomains in the melt align parallel to the electric field [51][52][53].…”
Section: Electric Fieldsmentioning
confidence: 99%
“…More recently, Gunkel et al [55] have developed a similar approach by including the composition fluctuation, and have arrived at…”
Section: Electric Fieldsmentioning
confidence: 99%